2018
DOI: 10.1080/13588265.2018.1478937
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the protective performance of neck braces for motorcycle riders: a finite-element study

Abstract: Neck protective devices for motorcyclists have been introduced fairly recently but there is no standard method to evaluate their performance. The goal of this study is to compare the response of riders' necks to direct impacts on the helmet with and without such a device. We investigate three common types of cervical injury mechanisms i.e. hyperflexion, hyperextension and lateral bending using FEM. The rotational movement of the head with respect to the torso, the neck shearing and axial loads and the stress d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…These devices are designed to reduce the vulnerability of the cervical spine by reducing the range of motion of the head/neck, and keeping it under physiological limits; they also distribute the impact energy on the shoulders [20]. The performance of these devices was recently investigated in [21,22]. These studies showed uncertainties regarding their protection effectiveness, thus confirming the need to develop a normalized evaluation procedure for such devices.…”
Section: Subjects Neck Braces and Powered Two-wheelersmentioning
confidence: 99%
“…These devices are designed to reduce the vulnerability of the cervical spine by reducing the range of motion of the head/neck, and keeping it under physiological limits; they also distribute the impact energy on the shoulders [20]. The performance of these devices was recently investigated in [21,22]. These studies showed uncertainties regarding their protection effectiveness, thus confirming the need to develop a normalized evaluation procedure for such devices.…”
Section: Subjects Neck Braces and Powered Two-wheelersmentioning
confidence: 99%